PERTUMBUHAN JAHE MERAH (Zingiber officinale var. Rubrum) PADA BEBERAPA KONSENTRASI DAN LAMA PERENDAMAN DALAM ZPT ATONIK - Mita Setyowati; Teuku Sarwanidas; Rizawati Rizawati (Universitas Teuku Umar, 2018)
Red Ginger (Zingiber officinale var. Rubrum) requested for the purposes of herbal medicine, industrial medicine and flavoring in both the domestic and export abroad. Development of ginger in wide scale with the optimal cultivation system so that its productivity increases can be made in intensifying planting materials by submersion use ZPT Atonik. This research aims to know the influence of concentration and long soaking in the ZPT Atonik against growth of Red ginger. This research was carried out at the experimental of Agriculture Facultyof Teuku UmarUniversity Aceh Barat. The material used is a local clone of Red ginger seeds from the village of Kuala Manyeu, Nagan Raya, ZPT Atonik, cow dung, manure polybags size 45x35 cm, pesticide Furadan and Dithane, as well as basic fertilizer (urea, KCl and SP-36). The experimental design used in this study was a randomized Design Group (RAK) factorial pattern 3 x 3 with 3 replicates. Factors examined are the concentration of ZPT Atonik consists of 3 levels i.e. without ZPT, 2 ml. l-1, and 4 ml. l-1 and long soaking consists of 3 levels, namely 10 minutes, 30 minutes and 50 seconds. The parameters observed were higher plants, the number of shoots per clump of leaves, the number and length of the leaf. Data analysis with her rangeand conducted further trials BNT on levels 5% if there is a noticeable influence. The results showed that there is no interaction between concentration and long soaking in the ZPT Atonik against all the parameters were observed. The best red ginger growth found on the concentration of ZPT Atonik 2 ml. l-1. The best red ginger growth is in long soaking treatment that is 10 minutes. Keywords: Red ginger, concentration, long soaking, ZPT Atonik.